Niveau De Contamination Du Poivron (Capsicum L., 1753) Par Les Pesticides - Moussa, Diarra; Léonce, Kouadio David; Narcisse, Aboua Kouassi; Baba, Soro Donafologo; Antoine, Kouadio; Sory, Traore Karim; Koné, Mamadou; Ardjouma, Dembélé (European Scientific Journal, ESJ, 2018)
The study was done on two species of peppers capsicumannuum and capsicum fructescens. It concerned ninety samples of these two species, collected during three countrysides in two localities of Côte d’Ivoire (Bouake and Dabou). These samples were handled by means of a liquid-phase leading chromatograph SHIMADZU with the aim of determining the residues of pesticides. The observed results revealed a contamination of both species : capsicum annuum and capsicum fructescens, indeed, six residues of pesticides (chlorothalonil, chlorpyrifos, carbendazim, maneb, dimethoate and lambdacyaholothrine) were detected in these two species distributed in four families of pesticides (organochlorines, organophosphates, carbamates and pyrethrinoïds). The analysis showed that pyrethrinoïdes with respective proportions of 76,17% and 75,95% in capsicum annuum and capsicum fructescens were the most important ; followed organophosphate with respective proportions of 10,93% and 20,04% in capsicum annuum and capsicum fructescens.The study also showed that the concentrations of residues of pesticides detected in the edible part (pericarp ) peppers are appreciably equal those found in the part inedible(pulp). However, the residues of pesticides detected in peppers of both localities have all average concentrations lower than the standards established by the Codex Alimentarius.